The Aston Programme Contribution to Organizational Research: A Literature Review. (8th March 2013) - Donaldson, Lex; Luo, Ben Nanfeng
<x xml:space="preserve">Abstract</x> This paper reviews the literature about the Aston Programme of organizational research, in particular, its studies of organizational structure. The intellectual commitments of the Aston Programme are explicated and contrasted with the then dominant traditions of organizational research. The methodology is explained, with its emphasis on quantitative variables, reliable scales and statistical methods. The way successive studies confirmed or challenged Weberian bureaucracy is discussed. The major structural scales and their short forms are described. The relationships among the structural variables and between them and the contextual variables of size, technology and public accountability are outlined. The generalizability of these relationships in organizational research across countries is considered. The paper offers a roughly chronological narrative in three phases: the original Aston study, the National study and then on to the many subsequent replication and extension studies and reviews of them. Some cognate organizational research studies are brought in that confirm the Aston Programme. The need to continue the Astonian Cartesian approach rather than the configurational approach is emphasized. In closing, the Aston legacy is briefly summated and a vision for a future Aston Programme is offered in an Epilogue.